Multiple production up to √s = 13 TeV with the generator GHOST adapted to cosmic ray simulation - Capdevielle Jean-Noël; Plebaniak Zbigniew; Szabelska Barbara; Szabelski Jacek (EPJ Web of Conferences, 2017)
The model HDPM of CORSIKA has been updated and developed on the base of the recent measurements by LHCb, CMS, TOTEM... The new model GHOST involving a 4-source production reproduces correctly the pseudorapidity distributions of charged secondaries and has been testified with the data in the mid and forward rapidity region, especially in the complex case of TOTEM and also with the recent measurements of CMS up to FX2 (9.2 · 1016 eV). Special calculations have been devoted to the semi-inclusive data playing an important role in the cosmic ray simulation (fluctuations in the earliest collisions, individual cascades and remarkable events). Taking into account the violation of KNO scaling, the negative binomial distribution has been used pointing out an asymptotic behaviour of total charged multiplicities at primary energies exceeding 40 TeV (7 · 1017 eV). The interpretation of the most recent measurements suggests for EAS generated by primary protons a larger production of muons and a cascade maximum at higher altitude than previously assumed.